Ohtahara II sydrome as a rare epileptic encephalopathy - Akhmadeeva L.R.; Vashkevich A.G.; Vorontsova L.M. (Саратовский научно-медицинский журнал, 2018)
We present information about Ohtahara II syndrome which is a rare epileptic encephalopathy, and our own clinical case: a 4-year old child with this disorder.